Causes of the Shortage of Physics Teachers in Croatia - Nataša Erceg; Lejla Jelovica; Vanes Mešić; Ljubiša Nešić; Ivana Poljančić Beljan; Patricija Nikolaus (MDPI AG, 2023)
Knowing the causes of the shortage of physics teachers in primary and secondary schools is necessary for the development of effective educational policies because the shortage of physics teachers is a global and persistent problem with negative consequences for the quality of education, but also for the survival of the physics profession as a whole. The aim of this study was to investigate, for the first time, the opinions of Croatian physics teachers on the causes of the deficit in their profession. For this purpose, we conducted a descriptive cross-sectional study using an online survey with Likert-type items and a constructed response item. A total of 390 respondents from all over Croatia participated in the survey, which is 29% of the total population of Croatian physics teachers in the 2022/2023 school year. According to their opinion, the causes of the shortage of Croatian physics teachers are related to the following: lack of incentives and support from the relevant institutions and bodies, the inadequacy of physics content in the curricula, the lack of motivation and negative attitude of students towards physics, impeded professional development, unequal opportunities, and challenges such as excessive workload. The results obtained provide a concrete basis for the development of an effective policy to solve the problem of the physics teacher shortage in Croatia and beyond by governments, universities, and schools.